Religious values based on local wisdom Munjungan tradition in Tukdana Village, Tukdana District, Indramayu Regency - Syarif Hidayatullah, Wahyudi; Herdianto Wahyu Pratomo; Maulana Jamaludin, Gilang (Departement of PAI, Universitas Majalengka, 2024)
Indonesian people have a vibrant cultural heritage, one example of cultural heritage that is still inherited by active heirs is traditional ceremonies or traditional ceremonies. Tukdana village, which is located in Tukdana District, Indramayu Regency, still has munjungan customs. In social and cultural contexts, munjungan can be used to enhance a sense of nationality, nationalism, and national identity. In the procession of this munjungan tradition, people gather from all social classes and social statuses, religions, beliefs, political groups, or political parties. Munjungan is an opportunity to love and care for one another while joining the community. There is a strong sense of familiarity, peace, and humanity. Indonesia looks more harmonious, prosperous, and calm because munjungan strengthens social relations